Grace Unveiled: The Charm of חסד in the Book of Ruth and Its Transformative Message for Christian Life - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mewengkang, Christie Garry (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
This article delves into the significance of Hesed, or loyal love, in the Book of Ruth, examining its theological implications for both human-divine relationships and interpersonal connections. It investigates how Hesed is depicted in the narrative of Ruth and Boaz, elucidating its role in worship and daily life. Methodologically, the study involves a close textual analysis of the Book of Ruth, employing a theological lens to interpret God's message of steadfast love. The findings reveal a profound understanding of God's inclusive and universal Hesed, with implications extending into the New Testament through the actions of Jesus Christ. This underscores the significance of God's unwavering love as a guiding principle in our relationships with both God and fellow humans, shaping a life reflective of the values encapsulated in Hesed.